Theological and psychological profile of Christian pilgrim - Rus, Mihaela; Rus, Ciprian-Vasile (Technium Social Sciences Journal, 2023)
Pilgrimage has always been an important element of spiritual and religious life for many people around the world, and this is certainly the case in Christianity. Pilgrimage in the Christian world represents a profound experience of seeking the meaning of life, religious identity, and faith. In this context, the theological and psychological profile of the Christian pilgrim are subjects of great interest. In addition to the literature review provided earlier, there is a growing body of research that focuses on the theological and psychological profiles of Christian pilgrims. Christian pilgrimage is a practice that has a long and rich history in Christianity, and is still a significant aspect of many Christian communities today.